Critical Thinking Disposition in the First- and Last-Year Medical Students and its Association with Achievement Goal Orientation - Maryam Baniasad; Abdolhussein Shakurnia (Kerman University of Medical Sciences, 2018)
Background Since medical students play an important role in public health system as well as the treatment of patients, the need for critical thinking in them is extensively felt. The current study aimed at evaluating the level of critical thinking disposition (CTD) in the first- and last-year medical students and its association with goal orientation in Ahvaz Jundishapur University of Medical Sciences in 2016. Methods The current cross sectional study used critical thinking disposition inventory (CTDI) developed by Rudd and Ricketts, and achievement goal questionnaire-revised (AGQ-R) developed by McGregor and Elliot to collect data. The questionnaires were distributed among 255 students of which 204 (80%) students completed them. Data were analyzed using -test and Pearson correlation coefficient. Results Of the 204 studied subjects, 104 were the first-year and 100 the last-year medical students. The mean age of the first and last year of medical students was 18.930.86 and 24.601.31 years, respectively. Moreover, 47 first-year and 66 last-year subjects were female. The mean score of CTD for the first- and last-year students were 69.82 ± 10.60 and 71.48 ± 11.86, respectively, lower than the average range. Based on the -test results, there was no significant difference between this group students (P = 0.310). The mean score of CTD and AGQ for all the study participants was 70.75 ± 11.12 and 28.22 ± 7.76, respectively; a significant correlation was observed between critical thinking disposition and achievement goal orientation (P = 0.001, r = 0.294). Conclusions The results of the current study indicated that the CTD score was lower than average range in the first- and last-year students; besides, lack of difference between first and last year students emphasized that educational processes should be propelled toward employment of approaches to promote and strengthen critical thinking disposition.